Clinical and immunological characteristics of a case with activated phosphoinositide 3-kinase δ syndrome 2 - Yang, Q Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2020)
Objective: To analyze the clinical and immunological characteristics of a patient with activated phosphoinositide 3-kinase δ syndrome 2 (APDS2). Methods: A retrospective analysis of clinical data, immune-related gene sequencing, imaging and laboratory findings of a patient with APDS2 admitted to Children's Hospital of Chongqing Medical University was performed. The absolute and relative numbers of peripheral lymphocyte subsets, immune cell subsets and phenotypes were detected by flow cytometry with the age matched healthy child or the patient's father as a control. Results: A female patient aged 6 years and 4 months old was firstly admitted due to paleness over one month and cough for 7 days in June 2017. The IgA (<0.067 g/L) decreased while the IgM (2.55 g/L) increased. The abdominal ultrasound found hepatomegaly (subcostal 1.7 cm) and splenomegaly (subcostal 3.6 cm), and gene sequencing revealed a heterozygous mutation in the PIK3R1 gene c.1425+1G>A. After the treatment with prednisone which was initiated with a dose of 10 mg/times, 3 times/d and continued and tapered over 7 months, the IgM decreased to normal (1.72 g/L), and the hepatomegaly (subcostal 0 cm) and splenomegaly (subcostal 0.5 cm) were improved. The patient was readmitted due to pale and sallow complexion for half a month in July 2019. The percentage of naive CD4(+)T (0.386) and naive CD8(+)T cells (0.271) were decreased while the percentage of terminally differentiated effector memory CD8(+)T cells (0.377) and transitional B cells (0.223) were increased. The mean fluorescence intensity (MFI) of phosphorylated protein kinase B (AKT) in CD3(+)T, CD4(+)T and CD8(+)T cells were higher in the patient (4 125, 5 213, 3 497) than those in her father (3 434, 3 312, 3 058). The percentage of follicular helper T cell (Tfh) (0.299), Th1 (0.491) and Th1-like cells (0.438) in the patient were higher than those in the healthy control (0.156,0.313,0.303), while the percentage of Th17 (0.126) and Th17-like cells (0.188) were lower than those in the healthy control (0.198, 0.315). And the percentage of CD57 in the patient (0.306) was also higher than that in the healthy control (0.246). Conclusions: The humoral immunity and cellular immunity of APDS2 patient are impaired to varying degrees. The steroid can improve the lymphoproliferation and autoimmune hemolytic anemia in this case